2018
DOI: 10.1111/acer.13934
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADHD in the Co‐Occurrence Between Heavy Alcohol Use and Depression Trajectories in Adulthood

Abstract: Background: Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with greater heavy alcohol use and depressive symptoms in adulthood. Yet, few studies have investigated whether childhood ADHD predicts an increased association between heavy drinking and depression in adulthood when this co-occurrence becomes more common. We examined associations among heavy alcohol use and depression longitudinally from ages 21 to 29 and whether these associations differed for those with or without childhood ADHD, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This hypothesis can be transposed to our own result, with the idea that frequent comorbid psychiatric conditions of inattention symptoms may explain why students with higher levels of inattention were more likely to report binge drinking. Note that a recent longitudinal study (Wang et al, 2019) tends to corroborate this idea, showing a significant association between depression and heavy drinking as well as increasing depression for adults with ADHD histories.…”
Section: Discussionmentioning
confidence: 93%
“…This hypothesis can be transposed to our own result, with the idea that frequent comorbid psychiatric conditions of inattention symptoms may explain why students with higher levels of inattention were more likely to report binge drinking. Note that a recent longitudinal study (Wang et al, 2019) tends to corroborate this idea, showing a significant association between depression and heavy drinking as well as increasing depression for adults with ADHD histories.…”
Section: Discussionmentioning
confidence: 93%
“…Recent systematic reviews and meta-analyses [ 10 , 11 ] estimated that ADHD might occur in nearly one out of six adults with BD, possibly anticipating its onset by about four years [ 11 ]. It is well known that ADHD itself might be correlated with AUD [ 12 , 13 ]. Previous longitudinal studies have shown that ADHD might have a significant impact on alcohol-related behaviors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ADHD itself might be correlated with AUD [ 12 , 13 ]. Previous longitudinal studies have shown that ADHD might have a significant impact on alcohol-related behaviors [ 13 , 14 ]. The high levels of impulsivity and sensation seeking that has been described among individuals with ADHD may significantly increase the risk of AUD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, adults with versus without ADHD are less likely to be married, report fewer familial connections, have less stable employment, and are less financially independent (Barkley, 2015; Biederman et al, 1993; Hechtman et al, 2016; Klein et al, 2012; Michielsen et al, 2015; Murphy and Barkley, 1996; Pelham III et al, 2020), which may afford relatively more time and opportunity for heavy drinking. These and other factors, such as increasing rates of depression among young adults with ADHD during this time period (Wang et al, 2019) and the manifestation of familial risk for alcoholism (Molina et al, 2016), may contribute to sustained heavy drinking even when their peers begin to decrease their drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Factors not examined herein may be important. These include a tightening of the significant association between depression and alcohol use over time for those with ADHD (Wang et al, 2019) and specific facets of impulsivity, including negative and positive urgency (Pedersen et al, 2016). This possibility necessitates longitudinal studies that extend further into adulthood, beyond the 20s, when ADHD‐related risk for alcohol use may more starkly differentiate individuals.…”
Section: Discussionmentioning
confidence: 99%